Peste des Petits Ruminants Virus-Like Particles Induce a Potent Humoral and Cellular Immune Response in Goats - Feihu Yan; Logan Banadyga; Yongkun Zhao; Ziqi Zhao; Zachary Schiffman; Pei Huang; Entao Li; Cuiling Wang; Yuwei Gao; Na Feng; Tiecheng Wang; Hualei Wang; et al. (Viruses, 2019)
Peste des petits ruminants is a highly contagious acute or subacute disease of small ruminants caused by the peste des petits ruminants virus (PPRV), and it is responsible for significant economic losses in animal husbandry. Vaccination represents the most effective means of controlling this disease, with virus-like particle (VLP) vaccines offering promising vaccine candidates. In this study, a PPRV VLP-based vaccine was developed using a baculovirus expression system, allowing for the simultaneous expression of the PPRV matrix (M), hemagglutinin (H), fusion (F) and nucleocapsid (N) proteins in insect cells. Immunization of mice and goats with PPRV VLPs elicited a robust neutralization response and a potent cellular immune response. Mouse studies demonstrated that VLPs induced a more robust IFN-γ response in CD4+ and CD8+ T cells than PPRV Nigeria 75/1 and recruited and/or activated more B cells and dendritic cells in inguinal lymph nodes. In addition, PPRV VLPs induced a strong Th1 class response in mice, as indicated by a high IgG2a to IgG1 ratio. Goat studies demonstrated that PPRV VLPs can induce the production of antibodies specific for F and H proteins and can also stimulate the production of virus neutralizing antibodies to the same magnitude as the PPRV Nigeria 75/1 vaccine. Higher amounts of IFN-γ in VLP-immunized animal serum suggested that VLPs also elicited a cellular immune response in goats. These results demonstrated that VLPs elicit a potent immune response against PPRV infection in small ruminants, making PPRV VLPs a potential candidate for PPRV vaccine development.